2019
DOI: 10.1021/jacs.9b04173
|View full text |Cite
|
Sign up to set email alerts
|

Highly Electroconductive Metal–Organic Framework: Tunable by Metal Ion Sorption Quantity

Abstract: This study has developed a simple and innovative approach to design a metal–organic framework (MOF) with tunable conductivity. The in situ amine functionalized TMU-60 [Zn­(OBA)­(L*)·DMF] has the potential of converting to a conductor due to the selective and fast sorption of cadmium ion. In order to precisely monitor the cadmium penetration to the framework pores, in addition to full kinetic and thermodynamic studies of sorption, the time-dependent effects of Cd­(II) penetration to MOF pores was taken by fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…The equivalent circuit mainly includes the elements: the equivalent series resistance (R s ), charge-transfer resistance (R ct ), the constant phase angle element (CPE), and Warburg resistance (W). [43] In the highfrequency region, the intercept value on the x-coordinate corresponds to the solution resistance R s , and the diameter of the semicircle corresponds to the reaction resistance R ct of faradaic reactions and EDLC. Among them, Co-Ni-B-S shows a little resistance, which is concordant for its excellent electrochemical performance ( Figure S14a, Supporting Information).…”
Section: Doi: 101002/adma201905744mentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent circuit mainly includes the elements: the equivalent series resistance (R s ), charge-transfer resistance (R ct ), the constant phase angle element (CPE), and Warburg resistance (W). [43] In the highfrequency region, the intercept value on the x-coordinate corresponds to the solution resistance R s , and the diameter of the semicircle corresponds to the reaction resistance R ct of faradaic reactions and EDLC. Among them, Co-Ni-B-S shows a little resistance, which is concordant for its excellent electrochemical performance ( Figure S14a, Supporting Information).…”
Section: Doi: 101002/adma201905744mentioning
confidence: 99%
“…The EIS spectrum is composed of a semicircle part in the high‐frequency region and a linear component in the low‐frequency region. The equivalent circuit mainly includes the elements: the equivalent series resistance ( R s ), charge‐transfer resistance ( R ct ), the constant phase angle element (CPE), and Warburg resistance ( W ) . In the high‐frequency region, the intercept value on the x ‐coordinate corresponds to the solution resistance R s , and the diameter of the semicircle corresponds to the reaction resistance R ct of faradaic reactions and EDLC.…”
mentioning
confidence: 99%
“…Recently, Rouhani et al provided a simple but innovative strategy to tune the conductivity of MOFs ( Figure ). [ 153 ] They found that in situ amine functionalized TMU‐60 [Zn(OBA)(L*)·DMF] could largely improve its conductivity owing to the sorption of cadmium ion. In addition, the conductivity could also be adjusted by controlling the amount of absorbed metal ions.…”
Section: The Design and Synthesis Of Conductive Mofsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are crystalline solids composed of metal ions coordinated by multifunctional organic molecules with a three-dimensional porous structure. The composition and structure of MOFs could be easily adjusted via the rational selection of the metal ion and organic molecule (Rouhani et al, 2019). Furthermore, they feature poor electrical conductivity and well-defined porous structure, allowing for fast ion diffusion (Zhu et al, 2019).…”
Section: Metal-organic Framework (Mofs) Mg Ion Solid Conductorsmentioning
confidence: 99%